High Sensitivity of Human Adipose Stem Cells to Differentiate into Myofibroblasts in the Presence of C. aspersa Egg Extract - Natalio García-Honduvilla; Alberto Cifuentes; Miguel A. Ortega; Arancha Delgado; Salvador González; Julia Bujan; Melchor Alvarez-Mon (Stem Cells International)
Introduction. Regeneration therapy using adipose-derived stem cells (ADSC) has been proposed in the treatment of skin aging. Myofibroblast plays a relevant role in the organization of the extracellular matrix of the damaged skin. A natural extract was derived from the eggs of the mollusk Cryptomphalus aspersa (e-CAF) that seems to play a role on skin repair. We have investigated the potential effects of e-CAF in the differentiation of ADSC. Materials and methods. ADSC were cultured in the absence or presence of e-CAF (50 and 200 μg/mL) for 24 hours and 7 days. Real-time cell assay, morphological, immunofluorescence, and RT-PCR techniques were used to evaluate the cell culture and expression of αSMA, collagen I, and tropoelastin. Results. e-CAF induced significant reduction in the rate of growth of ADSC from 24 hours to 7 days of culture. e-CAF also induced bigger sizes, higher levels of cytoplasmic refringence and complexity, and a more polyhedral morphological changes in the cultured ADSC. The protein and mRNA expression of αSMA was significantly increased in e-CAF-cultured ADSC. Conclusion. e-CAF promotes ADSC differentiation to myofibroblasts and should be considered as a potential agent for the prevention and treatment of skin aging.